Use of typical features like pitch criterion for the selection of the phenomenon of social and psychological outsider - Antsybor, A. (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2017)
The article deals with the most vivid and typical criterions and identify outsider outlook that can be used to identify people with severe symptoms of socio-psychological outsider. Describes and analyzes such common psychological phenomena like low self-esteem, which is confirmed in the social life and leads to the recognition of an outsider, a tendency to social compared to negative conclusions, loneliness, poor quality of life, level of activity, primarily social, the strength of the motives, will full voltage the level of frustration and depression, the level of self-efficacy. These criterions are presented in the form of a generalized table survey, with the possibility of differentiation in the high, medium and low levels of expression, it makes it possible to fix the presence outsider qualities and on that basis to conclude that man's belonging to the category of outsiders.
Keywords: low self-esteem; social comparison; isolation; poor quality of life; level of activity; the strength of the motives; the level of self-efficacy